2013
DOI: 10.7863/ultra.32.8.1443
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Sonographic Diagnosis of Superficial Masses

Abstract: Sonography has high accuracy in the evaluation of superficial masses, particularly lipomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 12 publications
2
48
0
Order By: Relevance
“…(5) and Wagner et al. (11) used a combination of both prospective and retrospective review of images. The retrospective review of static images is a common limitation of clinical studies into ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…(5) and Wagner et al. (11) used a combination of both prospective and retrospective review of images. The retrospective review of static images is a common limitation of clinical studies into ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…When referred for sonographic evaluation, ultrasonography has been shown to have variable accuracy, reportedly as high as 96% sensitivity, 97% specificity, and overall accuracy of 96% for the diagnosis of lipoma. 1 However, other investigators have reported lower numbers, ranging from 49% to 86% in overall accuracy. 4 In most cases, typical sonographic findings of a lipoma require no further evaluation other than periodic clinical follow-up.…”
Section: Benign Solid Masses Lipomamentioning
confidence: 96%
“…4 In one case series, 54% of all superficial masses referred for sonographic evaluation over a 3-year period were lipomas. 1 The sonographic appearance is typically of a well-circumscribed mass that can have variable echogenicity compared with the surrounding soft tissues. In the case series previously referred to, 59% of masses were isoechoic (Fig.…”
Section: Benign Solid Masses Lipomamentioning
confidence: 99%
See 2 more Smart Citations